2001
DOI: 10.1029/2000ja000335
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of electron beam generated waves resulting in transverse ion heating and filamentation of the plasma

Abstract: Abstract. We present here a systematic simulational study on electron beam driven waves and their consequences in terms of plasma electrodynamics. The study is performed by using three-dimensional particle-in-cell code, parallelized to simulate a large volume of plasma. Our simulation shows that an initial electron beam of finite radius with beam velocity along the ambient magnetic field triggers a series of events in the evolution of the waves and the plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…In contrast to the lack of heating seen here, we have shown that when a filamentary electron beam drives large-amplitude lower hybrid waves, the ions are significantly heated by nonlinearly-driven stochasticity (Singh et al, 2001c). We also point out that, even though the electron holes have significant perpendicular electric fields in their structure, they do not affect the ions.…”
Section: Propagation Velocitycontrasting
confidence: 41%
See 2 more Smart Citations
“…In contrast to the lack of heating seen here, we have shown that when a filamentary electron beam drives large-amplitude lower hybrid waves, the ions are significantly heated by nonlinearly-driven stochasticity (Singh et al, 2001c). We also point out that, even though the electron holes have significant perpendicular electric fields in their structure, they do not affect the ions.…”
Section: Propagation Velocitycontrasting
confidence: 41%
“…Instead, large-amplitude lower-hybrid waves and their decay into Alfvén resonance-cone waves at frequencies below the ion cyclotron frequency dominate the plasma (Singh et al, 2001c). Even in this case, the low-frequency waves below the ion cyclotron frequency accompany a filamentary density structure like that shown in Fig.…”
Section: Propagation Velocitymentioning
confidence: 94%
See 1 more Smart Citation
“…Useful information about the life-time of the electronholes and ion heating is provided by the 2-D and 3-D particle simulations of the electron-beam driven instabilities (Omura et al, 1999;Goldman et al, 2000;Singh et al, 2001b). 3-D simulations of the electron-beam driven electron holes reveal that initially a large number of electron holes are formed.…”
Section: Discussionmentioning
confidence: 99%
“…It is seen that the initial evolution to bipolar structures in the xdirection, the direction of the ambient magnetic field, is followed by the excitation of whistlers, which dominate at later times. Singh et al (2001b) have performed 3-D particle simulation of electron beam driven instabilities to explain the characteristics of the solitary structures observed on the auroral field lines. Figure 7 shows some results of their simulations for a finite-sized fast electron beam with V b /V te = 8.…”
Section: Bgk Modes/phase Space Holesmentioning
confidence: 99%